2023
DOI: 10.1177/10711007231162825
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Drilling, Ossoscopy, and Autologous Bone Grafting: An Alternative Technique for Treatment of Osteochondral Lesion of the Talus Stage 2 and 3 in Adults

Abstract: Background: Symptomatic osteochondral lesions of the talus (OLTs) often require surgical intervention. There are various surgical methods. A generally valid, stage-dependent therapeutic algorithm does not exist. The aim of our study is to show long- term results of an alternative technique that combines retrograde drilling, debridement performed under arthroscopic visualization, and autologous bone grafting. Methods: The surgical technique was performed in 24 patients with medial or lateral OLTs, and the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In a retrospective case series, Huber et al 18 reported the long-term results of an alternative technique for OLTs with a mean size of 0.9 ± 0.3 cm 2 that combines retrograde drilling, debridement performed under arthroscopic visualization (ossoscopy) without violating the cartilage, and autologous bone grafting. At a mean follow-up of 89 months, this technique resulted in good outcomes with excellent patient satisfaction, especially in OLT stages 2 and 3.…”
Section: Osteochondral Lesions Of the Talusmentioning
confidence: 99%
“…In a retrospective case series, Huber et al 18 reported the long-term results of an alternative technique for OLTs with a mean size of 0.9 ± 0.3 cm 2 that combines retrograde drilling, debridement performed under arthroscopic visualization (ossoscopy) without violating the cartilage, and autologous bone grafting. At a mean follow-up of 89 months, this technique resulted in good outcomes with excellent patient satisfaction, especially in OLT stages 2 and 3.…”
Section: Osteochondral Lesions Of the Talusmentioning
confidence: 99%
“…Huber et al 6 have provided us with further evidence of the validity of retrograde drilling of cystic OLT and insertion of autologous bone graft. However, further questions remain in our struggle to treat these difficult lesions.…”
mentioning
confidence: 98%
“…The literature can be confusing regarding the best treatment method, especially in an osteochondral lesion with an adjoining cyst. 10 In this issue, Huber et al 6 have described their results utilizing retrograde drilling, ossoscopy, and autologous bone grafting of osteochondral lesions of the talus. This technique was used in 24 patients, with the largest lesion 1.4-cm 2 with a mean follow-up of 89 months.…”
mentioning
confidence: 99%
See 2 more Smart Citations